O setor leptônico neutro e a violação de CP - Chaves, Tiago Leite [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
We present a review of the main experiments which have observed a deﬁcit in the solar neutrino ﬂux, leading to the establishment of the Solar Neutrino Puzzle. Also, we comment on the atmospheric neutrino anomaly. The study of these two systems suggest that a ﬂavor conversion mechanism must be a solution for both deﬁcits. This mechanism, known also as neutrino oscillation, requests that mass and mixing have to be introduced in the neutral leptonic sector. After that we have studied neutrino oscillation in vacuum and in matter. Next, in viewing of the potential importance of neutrino masses, as suggested by all neutrino oscillation data, we have studied the neutral leptonic sector describing some illustrative neutrino mass models. Finally, we have studied CP violation in neutrino oscillation. First, we deﬁne the Dirac and Majorana CP violation phases. Second, we discuss in some details the process of neutrinoless double beta decay 0'nü' 'beta beta' showing that it is the best way to provide an evidence for revealing the Dirac or Majorana neutrino character. In particular, we have shown that CP violation in neutrino oscillation is completely insensitive to that question, i.e., if neutrinos are Dirac or Majorana particles. We have also discussed the importance of the mixing parameter 'teta IND. 13' for detecting CP violation in the neutral leptonic sector. To conclude, we comment brieﬂy on both Double CHOOZ and Angra Project experiments. These experiments are aimed to measure 'teta IND. 13' improving the present limits constrained by CHOOZ

Neste trabalho, apresentamos um resumo dos principais experimentos que constataram a existência de um déﬁcit no ﬂuxo de neutrinos solares, levando assim, ao estabelecimento do chamado Problema dos Neutrinos Solares (PNS). Ainda que brevemente, abordamos a anomalia dos neutrinos atmosféricos. O estudo destes dois sistemas sugere que um mecanismo de conversão de sabor deve ser a solução para ambos. Esse mecanismo, também conhecido como oscilação de neutrinos, requer que massa e mistura sejam introduzidos no setor leptônico neutro. Estudamos a propagação do neutrinos no vácuo e na matéria. Posteriormente, em vista da potencial importância das massas dos neutrinos, como sugerem os experimentos de oscilação, estudamos o setor leptônico neutro descrevendo alguns modelos de massa para neutrinos a título de ilustração. Na sequência, estudamos a possibilidade de violação de CP na oscilação de neutrinos. Primeiramente, deﬁnimos as fases de violação de CP de Dirac e de Majorana. Discutimos rapidamente o decaimento 0'nü' 'beta beta' mostrando que estaé a forma mais promissora de testar a natureza de Majorana dos neutrinos. Em particular, mostramos que a violação de CP na oscilação de neutrinos é completamente insensível à mesma questão, ou seja, se os neutrinos são partículas de Dirac ou Majorana. Avaliamos, de forma qualitativa, a importância do ângulo 'teta IND. 13' para a detecção da violação de CP no setor leptônico neutro. Por ﬁm, citamos, como exemplos, os experimentos Double CHOOZ e o Projeto Angra, no Brasil, ambos desenvolvidos com o objetivo de melhorar os limites impostos pelo CHOOZ paraθ13
Keywords: Neutrinos solares; Violação de CP (Física nuclear); Solar neutrinos